1979
DOI: 10.1172/jci109559
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococci-induced Human Platelet Injury Mediated by Protein A and Immunoglobulin G Fc Fragment Receptor

Abstract: A B S T R A C T Bloodstream infections with staphylococci are accompanied by thromboembolic complications. We have studied the mechanism of the interaction of staphylococci with human blood platelets.Staphylococci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Interestingly, injury to human platelets by S. aureus has recently been shown also to involve interactions of cell wall protein A, IgG, and platelet Fc receptors (46).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, injury to human platelets by S. aureus has recently been shown also to involve interactions of cell wall protein A, IgG, and platelet Fc receptors (46).…”
Section: Discussionmentioning
confidence: 99%
“…aureus predominantly uses multiple cell wall surface proteins to interact with platelets to trigger their activation. Early studies by Hawiger et al demonstrated that S. aureus cell wall protein A acts as a receptor for specific anti-staphylococcal antibodies which in turn bind FcγRIIa on platelets (Hawiger et al, 1979). This interaction triggers an intracellular signal that leads to granule release and platelet aggregation.…”
Section: Platelet-bacterial Interactions: the Staphylococcusmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) was loaded with [14C]serotonin (0.05 MCi/ml) and then platelets radiolabeled with serotonin were separated from free amine and from plasma proteins as described previously (26). Secretion of ['4C]serotonin was measured at 370C with stirring for the specified times in the presence of imipramine (1.5 Mg/ml).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was stopped by chilling the platelets on ice and adding 0.3% p-formaldehyde in 2 mM EDTA before centrifugation in a microcentrifuge for 15,000 g for 2 min (27). Secretion was calculated as previously described (26).…”
Section: Introductionmentioning
confidence: 99%